BIOFEEDBACK APPLICATION FOR PREGNANT WOMAN TRAINING UNDER MONITORING OF MOTHER – FETUS SYSTEM CONDITION - A. A. Khlopova; Ya. S. Pekker; I. V. Tolmachev (Бюллетень сибирской медицины, 2013)
Raining influence with biofeedback on system mother fetus was investigated. The technique of biofeedback training for the pregnant women was developed, which had main objective to control of parameters of vegetative nervous system by means of breath. The technique was tested on a group of pregnant wo men on term of a gestation of 32–35 weeks. It is established: change of a functional condition of mother influences level of sympathetic regulation of a heart rhythm of a fetus.